The Processing of LDPE Plastic Waste into Renewable Fuel Using Waste Motor Oil - Alex Surapati; Angky Puspawan; Yanolanda Suzantry Handayani; Fitrilina (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
The increase in population causes an increasing amount of solid waste, especially plastic waste. Plastic waste that cannot be decomposed in nature increases its number and causes environmental pollution. The research aimed to process plastic waste into alternative fuel oil using waste motor oil. The research methods consisted of designing a plastic waste processing device using waste motor oil as fuel and testing the device with a plastic burning process using a processing machine. The plastic waste processing device was produced in the form of a stove that functions to heat plastic waste fueled by waste motor oil using an electric blower to generate pressure into the reactor. The heating process produces steam flowing and processing in a distillation tube to produce oil. The resulting temperature was 140oC and could melt plastic waste, but there were still burning residues. The distillation produced two types of fuel oil, yellow and black.